The Chameleon Effect: Characterization Challenges Due to the Variability of Nanoparticles and Their Surfaces - Baer, Donald R. (Frontiers in Chemistry, 2018)
Nanoparticles in a variety of forms are increasing important in fundamental research, technological and medical applications, and environmental or toxicology studies. Physical and chemical drivers that lead to multiple types of particle instabilities complicate both the ability to produce, appropriately characterize, and consistently deliver well-defined particles, frequently leading to inconsistencies, and conflicts in the published literature. This perspective suggests that provenance information, beyond that often recorded or reported, and application of a set of core characterization methods, including a surface sensitive technique, consistently applied at critical times can serve as tools in the effort minimize reproducibility issues.